2020
DOI: 10.1186/s41065-020-00121-5
|View full text |Cite
|
Sign up to set email alerts
|

No association between interleukin-18 levels and risk of cardiovascular disease: A Mendelian randomization study

Abstract: Objective: In this study, Mendelian randomization method was used to determine whether there was a causal association between inflammatory cytokine IL-18 and cardiovascular disease risk. Methods: We performed a meta-analysis to evaluate the association between IL-18-137G/C and -607C/A polymorphisms and phenotype of IL-18 levels, and also the risks of CVD. All the literatures were searched before September 30, 2019. The logistic regression and linear regression were used to evaluate between IL-18 level and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There is high heterogeneity in both susceptibility to and severity of SARS-CoV-2 infection, with clinical severity [ 1 , 2 ] ranging from asymptomatic infection to life-threatening respiratory failure and death [ 3 ]. Epidemiological studies using both retrospective and prospective cohorts of different sizes and from multiple countries have reported evidence that underlying cardiometabolic conditions [ 4 29 ] may be associated with an increased risk of severe COVID-19 illness (i.e., hospitalization, intubation, mechanical ventilation, or death [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%
“…There is high heterogeneity in both susceptibility to and severity of SARS-CoV-2 infection, with clinical severity [ 1 , 2 ] ranging from asymptomatic infection to life-threatening respiratory failure and death [ 3 ]. Epidemiological studies using both retrospective and prospective cohorts of different sizes and from multiple countries have reported evidence that underlying cardiometabolic conditions [ 4 29 ] may be associated with an increased risk of severe COVID-19 illness (i.e., hospitalization, intubation, mechanical ventilation, or death [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%
“…There is high heterogeneity in both susceptibility and severity of SARS-CoV2 infection with clinical severity 1,2 ranging from asymptomatic carriers to life-threatening respiratory failure and death 3 . Epidemiological studies using both retrospective and prospective cohorts of different sizes and from multiple countries have reported evidence that underlying cardiometabolic conditions 4-29 may be associated with an increased risk of severe COVID-19 illness (i.e., hospitalization, intubation, mechanical ventilation or death 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the adaptive immune system is involved in the development of atherosclerosis, the importance of IL-18 is considered crucial, especially when we focus on CKD-related atherosclerosis and its clinically relevant consequences [ 28 ]. Although data on the role of IL-18 in predicting coronary events are contradictory [ 29 , 30 ], many studies have shown its utility as a strong independent predictor of death from CV causes in patients with coronary artery disease regardless of the clinical status at admission [ 26 , 31 , 32 ]. This strongly supports the evidence of an IL-18-mediated inflammatory process, leading to the acceleration and vulnerability of the atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 99%